Les interprètes japonais en Algérie - Nohara, Michihiro (Meta, 1988)
SummarySince the end of the sixties, numerous Japanese contractors have been active in heavy industry work in Algeria and other North African countries. This has opened a large market for Japanese-French liaison interpreters. Such interpreters are hired by specialized agencies in Europe and Japan. With one or two exceptions, they are Japanese nationals. Most of them are young and have no previous experience as interpreters. Neither are they properly briefed before they are sent to the site, but they become proficient in their work with experience. Their tasks range from interpreting at various levels to translation and even participation in negotiations and report drafting. Material working conditions are comparatively good, but the duration of contracts is short and long-term stability of employment is uncertain. The precariousness of interpreting jobs and the temporary nature of the Japanese companies' contracting work in North Africa make this activity a provisional and highly volatile one. Japanese liaison interpreters in North Africa do not feel like professional interpreters and do not aspire to become professionals.